4D microprinting of dual-shape and triple-shape memory polymers [data] - Flórido Martins, Lilliana; Spiegel, Christoph A.; Blasco, Eva (Universität, 2026)
4D microprinting of shape memory polymers (SMPs) offers high structural design freedom alongside the smart characteristics of SMPs. However, functionality has so far been limited to dual-shape memory behavior, while a triple-shape memory effect - allowing access to multiple temporary shapes - remains unexplored for 4D microprinted SMPs. Here, we present an approach based on photocrosslinkable semicrystalline polymers offering access to two ink formulations for the fabrication of dual- and triple-shape memory microstructures via multiphoton laser printing. Printing parameters are optimized for generation of complex 3D microarchitectures with high printing precision and shape fidelity and thermal characterization establishes protocols for assessing the shape memory effects. All structures show remarkable shape memory performance featuring stable shape fixation and repeatable full recovery to the original structure. Notably, triple-SMP structures store an additional temporary shape enabling sequential two-directional actuation holding great potential for the next generation of soft microrobots and adaptive microsystems.
Gefördert durch: Deutsche Forschungsgemeinschaft: EXC-2082/1-390761711, INST35/1503-1FUGG; Carl Zeiss Foundation: Carl-Zeiss-Foundation-FocusHEiKA; Ministerium für Wissenschaft, Forschung und Kunst Baden-Württemberg: SDS@hd
Gesehen am 19.01.2026
Keywords: Forschungsdaten; Datenbank